PENGARUH TINGKAT SUKU BUNGA DAN NILAI TUKAR IDR/USD TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR TEKNOLOGI TAHUN 2020-2023 YANG TERDAFRAR DI BURSA EFEK INDONESIA - Mendur, David Reinal; Martono, Samuel (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to analyze the impact of interest rates and the IDR/USD exchange rate on the stock prices of technology sector companies listed on the Indonesia Stock Exchange during the 2020-2023 period. This research focuses on how fluctuations in interest rates and exchange rates influence investment decisions and stock prices in the technology sector. The method used in this study is secondary data collection. This research employs a combination of cross-sectional and time-series data for analysis. Descriptive analysis is conducted to provide a general overview of the collected data without drawing generalized conclusions. The findings indicate that high interest rates can pose challenges for companies in meeting their financial obligations, which in turn can affect profitability and stock prices. Additionally, changes in monetary policy, such as interest rate hikes, have a significant impact on the technology sector, highlighting the importance of understanding macroeconomic dynamics in the context of investment. The conclusion of this study confirms that both interest rates and exchange rates have a significant influence on the stock prices of technology sector companies in Indonesia. This research is expected to provide insights for investors and stakeholders in making better investment decisions in the Indonesian capital market.